Analysis Of Factors Affecting Provincial Minimum Wages In Indonesia - Richardo Simanjuntak; Yefriza Yefriza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this study is to analyze the factors that affect the minimum wage across different provinces in Indonesia. The study examines secondary data from Indonesia's Central Statistics Agency for the period 2018-2022, encompassing 34 provinces. The dependent variable in this study is the minimum wage of each province, while the independent variables used in this study are the need for a decent living, inflation, gross domestic product, and consumer price index. The data analysis method applied is panel data regression analysis with a random effect model. The research findings indicate that a higher standard of living, an increase in gross domestic product, and a rise in the consumer price index have a positive and significant effect on the minimum wage of each province. However, inflation does not appear to have a significant impact on the minimum wage of each province.